2023
DOI: 10.3389/fonc.2023.1247879
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of ramucirumab plus docetaxel in the treatment of patients with non-small cell lung cancer after immunotherapy: a systematic literature review

Edward B. Garon,
Carla Visseren-Grul,
Maria Teresa Rizzo
et al.

Abstract: IntroductionIn the REVEL trial, ramucirumab plus docetaxel demonstrated significant improvements in overall survival (OS), progression-free survival (PFS), and overall response rate (ORR) compared with placebo plus docetaxel for treatment of metastatic non-small cell lung cancer (NSCLC) that progressed during or after platinum-based chemotherapy. Since the approval of ramucirumab plus docetaxel, immune checkpoint inhibitors (ICIs), either as single agents or in combination with chemotherapy, have become the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(362 reference statements)
0
0
0
Order By: Relevance
“…A systematic review of 10 studies suggests a numerical better PFS of docetaxel plus ramucirumab in prior exposed patients to ICI than in those naïve to these compounds (5.7 vs. 3.8 months) with statistical significance in two trials (p = 0.012 and p = 0.041). However, according to this publication, docetaxel plus ramucirumab could not offer OS advantage in ICI pretreated patients [33]. Hence, another retrospective observational study, including 1439 patients, reported that patients treated with chemotherapy with or without anti-angiogenics after ICIs had better ORR [HR 1.71 (1.19-2.46); p = 0.004] without any OS [HR 1.05 (0.86-1.28), p = 0.63] and PFS advantage [HR 0.95 (0.8-1.12), p = 0.55], compared to patients ICI-untreated [34].…”
Section: Chemotherapy Plus Anti-angiogenic Agentsmentioning
confidence: 87%
“…A systematic review of 10 studies suggests a numerical better PFS of docetaxel plus ramucirumab in prior exposed patients to ICI than in those naïve to these compounds (5.7 vs. 3.8 months) with statistical significance in two trials (p = 0.012 and p = 0.041). However, according to this publication, docetaxel plus ramucirumab could not offer OS advantage in ICI pretreated patients [33]. Hence, another retrospective observational study, including 1439 patients, reported that patients treated with chemotherapy with or without anti-angiogenics after ICIs had better ORR [HR 1.71 (1.19-2.46); p = 0.004] without any OS [HR 1.05 (0.86-1.28), p = 0.63] and PFS advantage [HR 0.95 (0.8-1.12), p = 0.55], compared to patients ICI-untreated [34].…”
Section: Chemotherapy Plus Anti-angiogenic Agentsmentioning
confidence: 87%
“…Currently, there is no basis for implementing this type of treatment in clinical practice. There is a need for new drugs that act on other immunotherapy targets or combine known molecules with antiangiogenic drugs [53][54][55][56]. It is optimal to qualify patients for clinical trials with new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The MW is 146 kDa, which is similar to bevacizumab. It is used mainly in oncological contexts, including gatric, colorectal, non-small cell lung cancers, and hepatocarcinoma [18][19][20]. The safety of intraocular injection of ramucirumab has not yet been extensively tested.…”
Section: Vegfi Belonging To the Antibodies/chimeric Proteins Categorymentioning
confidence: 99%